Solution processing of TiO2 compact layers for 3rd generation photovoltaics - Cecile Charbonneau (Ceramics International, 2016)
In this study, we introduce a new method for the deposition of TiO2 compact layers which involves the deposition of a wet film of an inorganic titanium (IV) precursor followed by fast hydrolytic conversion to crystalline TiO2 under near infrared radiative (NIR) treatment. With this, we aim to provide a scalable alternative to methods conventionally employed in laboratories for the fabrication of 3rd generation photovoltaic devices, such as high temperature pyrolysis or spin coating of organic titanium (IV) precursors. Optimization of our solution process is presented in detail. Structural features and crystalline properties of solution processed compact layers are characterized by FEG-SEM imaging and x-ray diffraction analyses and compared to compact layers produced by conventional laboratory techniques. Minimization of electron recombination is evaluated in standard liquid I-/I3- dye-sensitized solar cells (DSC). The results show that a compact, homogenous, high coverage yield crystalline TiO2 anatase layer can be produced by sequential deposition of 2–3 solution processed titanium oxide layers, each in under 30 s. In standard liquid I-/I3- DSC the solution processed compact layers strongly increased the electron lifetime, τn, when compared to cells prepared on a bare FTO substrate.